Table of Content - - (Journal of Risk and Crisis Management, 2024)
Table of Content: 1. The impact of strategic control on improving crisis management efficiency in Jordanian industrial companies Salem Muhammad Al-Hababi 2. The Situation of Crisis Management in the Holy Capital Secretariat in Light of the Corona Covid-19 Pandemic and its Impact on Community Service During the Years (2019 to 2020) Muwaffaq bin Ahmed Al-Osaimi 3. The role of risk and crisis management in achieving development in the tourism sector Dr. Ibrahim Hassan Tawfick, Prof. Mohamed Fathy Yousif, Prof. Bahlol Ahmed Salem 4. Administrative empowerment strategy and its role in crisis management and exceptional circumstances From the point of view of the supervisory leaders of the Coastal Municipalities Water Utility in the Gaza Strip governorates Dr. Muhammad Mustafa Abu Mustafa, Dr. Hammad Mahmoud Al-Raqab 5. The Impact of Syrian Displacement on the Water and Health Sector and Urban Change in Irbid, Jordan Amani Mohammad Salem Bani Khalaf, Mohd Khairul Amri Kamarudin